Localization and Expression of Nuclear Factor of Activated T-Cells 5 in Myoblasts Exposed to Pro-inflammatory Cytokines or Hyperosmolar Stress and in Biopsies from Myositis Patients - Herbelet, Sandrine; De Vlieghere, Elly; Gonçalves, Amanda; De Paepe, Boel; Schmidt, Karsten; Nys, Eline; Weynants, Laurens; Weis, Joachim; Van Peer, Gert; Vandesompele, Jo; Schmidt, Jens; De Wever, Olivier; et al. (Frontiers in Physiology, 2018)
Aims: Regeneration in skeletal muscle relies on regulated myoblast migration and differentiation, in which the transcription factor nuclear factor of activated T-cells 5 (NFAT5) participates. Impaired muscle regeneration and chronic inflammation are prevalent in myositis. Little is known about the impact of inflammation on NFAT5 localization and expression in this group of diseases. The goal of this study was to investigate NFAT5 physiology in unaffected myoblasts exposed to cytokine or hyperosmolar stress and in myositis. Methods: NFAT5 intracellular localization and expression were studied in vitro using a cell culture model of myositis. Myoblasts were exposed to DMEM solutions enriched with pro-inflammatory cytokines IFN-γ with IL-1β or hyperosmolar DMEM obtained by NaCl supplementation. NFAT5 localization was visualized using immunohistochemistry (IHC) and Western blotting (WB) in fractionated cell lysates. NFAT5 expression was assessed by WB and RT-qPCR. In vivo localization and expression of NFAT5 were studied in muscle biopsies of patients diagnosed with polymyositis (n=6), dermatomyositis (n=10), inclusion body myositis (n=11) and were compared to NFAT5 localization and expression in non-myopathic controls (n=13). Muscle biopsies were studied by means of quantitative IHC and WB of total protein extracts. Results: In unaffected myoblasts, hyperosmolar stress ensues in NFAT5 nuclear translocation and increased NFAT5 mRNA and protein expression. In contrast, pro-inflammatory cytokines did not lead to NFAT5 nuclear translocation nor increased expression. Cytokines IL-1β with IFN-γ induced colocalization of NFAT5 with histone deacetylase 6 (HDAC6), involved in cell motility. In muscle biopsies from dermatomyositis and polymyositis patients, NFAT5 colocalized with HDAC6, while in IBM, this was often absent. Conclusions: Our data suggest impaired NFAT5 localization and expression in unaffected myoblasts in response to inflammation. This disturbed myogenic NFAT5 physiology could possibly explain deleterious effects on muscle regeneration in myositis.